2019
DOI: 10.5755/j01.eie.25.3.23678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control of Low-Voltage Ride-Through Capability Improvement for PMSG Based on an NPC Converter Using an Interval Type-2 Fuzzy Logic System

Abstract: Wind farms must be linked to the grid during the voltage sag. Therefore, the improvement of low-voltage ride-through (LVRT) capability of wind turbine (WT) is a vitally issue. Protection system based on an interval type-2 fuzzy logic system (IT-2 FLC) is presented to improvement of LVRT capability of permanent magnet synchronous generator (PMSG) based on WT during the voltage dip. The presented control system prevents the power converters from the damaging effects of over-voltage during LVRT time. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, when the efficiency of the motors is considered, it is concluded that the efficiency of the Induction Motor is 89.35 %, which is in the range of IE1 efficiency class, while that for the novel SynRM is 95.11 %, which is in the range IE4 efficiency class. The design of a new rotor with substantially lower total loss due to no rotor copper loss in SynRM [36], [37].…”
Section: E Comparison Of 22 Kw Synrm and Immentioning
confidence: 99%
“…However, when the efficiency of the motors is considered, it is concluded that the efficiency of the Induction Motor is 89.35 %, which is in the range of IE1 efficiency class, while that for the novel SynRM is 95.11 %, which is in the range IE4 efficiency class. The design of a new rotor with substantially lower total loss due to no rotor copper loss in SynRM [36], [37].…”
Section: E Comparison Of 22 Kw Synrm and Immentioning
confidence: 99%
“…The control scheme is achieved from the stability study of Lyapunov's approach. In [22], the authors applied interval type-2 FLC to regulate the rotor and stator currents to control the rotor and stator voltages.…”
Section: Introductionmentioning
confidence: 99%
“…In the VS-WECS configuration, various generators, such as Doubly-Fed Induction Generators (DFIG) and Permanent Magnet Synchronous Generators (PMSG) are employed. Nevertheless, PMSGs have undergone significant developments recently and are widely preferred for their advantages like lightweight, low noise, high power density, efficiency, low maintenance cost, and gearless operation [5]- [7]. Therefore, the authors practice on PMSG-based VS-WECS in this paper.…”
Section: Introductionmentioning
confidence: 99%